ANALYSIS OF THE INFLUENCE OF PRODUCT QUALITY, PROMOTIONS AND LOCATION ON PURCHASE DECISIONS NATURAL STONE CRAFTS AT NATURAL STONE RAINBOW STONE - Jimmy Indomora; J.E. Sutanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Purchase Decision is the selection of various alternatives in accordance with certain interests by establishing an option that is considered the most profitable for consumers. Therefore this research was conducted to find out how product quality, location, and promotion affect Purchase Decisions. This research was conducted on 89 respondents who had made purchases at Ranbow Stone Batu Alam at least twice. The results of this study prove that product quality, location, and promotion have a significant positive effect on Purchase Decisions. Product quality variable (X1) is the most influence to Purchase Decision (Y) with coeffient value 0,30, and then follow with promotion variable (X3) with coeffient value 0,24, and location variable with coeffient value 0.13. Through F-test, it is found that product quality, location, and promotion have significant influence towards purchase decision simultaneously.